Effect of hydrogen addition on the deposition of titanium nitride thin films in nitrogen added argon magnetron plasma. (4th May 2016) - Saikia, P; Bhuyan, H; Diaz-Droguett, D E; Guzman, F; Mändl, S; Saikia, B K; Favre, M; Maze, J R; Wyndham, E
Abstract: The properties and performance of thin films deposited by plasma assisted processes are closely related to their manufacturing techniques and processes. The objective of the current study is to investigate the modification of plasma parameters occurring during hydrogen addition in N2 + Ar magnetron plasma used for titanium nitride thin film deposition, and to correlate the measured properties of the deposited thin film with the bulk plasma parameters of the magnetron discharge. From the Langmuir probe measurements, it was observed that the addition of hydrogen led to a decrease of electron density from 8.6 to 6.2 × (10 14 m −3 ) and a corresponding increase of electron temperature from 6.30 to 6.74 eV. The optical emission spectroscopy study reveals that with addition of hydrogen, the density of argon ions decreases. The various positive ion species involving hydrogen are found to increase with increase of hydrogen partial pressure in the chamber. The thin films deposited were characterized using standard surface diagnostic tools such as x-ray photoelectron spectroscopy (XPS), secondary ion mass spectrometry (SIMS), x-ray diffraction (XRD), Raman spectroscopy (RS), scanning electron microscopy (SEM) and energy dispersive x-ray spectroscopy (EDS). Although it was possible to deposit thin films of titanium nitride with hydrogen addition in nitrogen added argon magnetron plasma, the quality of the thin films deteriorates with higher hydrogen partial pressures.